The study of family planning practice during and post Covid-19 pandemic crisis among married couples in Johor, Malaysia - Masazlin, Nurul Syakinah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
The current contraceptive prevalence rate in Malaysia is 52.2% which it is slightly lower than world’s CPR which was 60%. It is essential for married couples to practice family planning (FP) to prevent mortality and fatality occur among newborns, young mothers and high risk age group. A cross-sectional online survey was conducted among married couples in Johor, Malaysia from March 2022 until May 2022. A total of 240 respondents which are married couples were willingly participate in this study via online (GoogleForm). The data was collected using self-administered questionnaire that require the respondents to complete all of the three section. The mean age of the respondents was 34 years old (SD=7.759), with age range between 18 to 49 years old. Pearson’s Chi-Square test was used to determine the association of the selected factors to the changes of FP practice. Results revealed that the prevalence rate of FP practice was higher post COVID-19 pandemic crisis (42.9%) compared to FP practice during COVID-19 pandemic crisis (32.9%) in Johor, Malaysia. The result also shows that there is no significant association between all the selected factors- education level, locality, financial crisis, and access to services; to the changes of FP practice except for marriage duration (p=0.016) among the married couples that participate in this study. The conclusion for this study is the FP practice post COVID-19 is high among the married couples in Johor, Malaysia and marriage duration is associated with the changes of FP practice. The importance for FP practice should be given to all the married couple since young age of marriage to prevent and decrese the rate of occurrence of unmet pregnancy.